ANALISIS PELAKSANAAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 DAN PERATURAN MENTERI KEUANGAN NOMOR 215/PMK.03/2018 - R. Soerjatno; Levi Martantina (Jurnal Bisnis Terapan, 2019)
Tax is one of the country income sources to develop a nation in achieving general welfare. Fundamentally, all implementation rules of the Taxation Law are for convenience for taxpayers, because with such convenience it is expected that tax compliance will continue to increase. Likewise, the enactment of Government Regulation Number 23 of 2018 in addition to lightening of the tax burden relief for taxpayers because previously with Government Regulation Number 46 of 2013 it was stipulated that the tax rate was 1%, but in mid2018 Government Regulation number 46 was revoked and replaced with Regulation Government number 23 of 2018 concerning income tax on income from business received or obtained by taxpayers who have certain gross circulation which sets a tax rate of 0.5%, so there is a tax relief in the form of a reduction in the tax rate of 0.5%. In Government Regulation of 2018 number 23, it is also stipulated that Taxpayers may choose not to count using Government Regulation of 2018number 23, but apply the Article 25 paragraph (7) of the Income Tax Law which we briefly call General Income Tax. Regarding the calculation of general income tax, it has been set in the Minister of Finance Regulation Number 215 / PMK.03 / 2018 which will take effect on December 1, 2018. Based on the discussion of the Minister of Finance Regulation Number 99 / PMK.03 / 2018 as the implementation rule of Government Regulation Number 23 of 2018, which the installment calculation of Income Tax Article 25 refers to Minister of Finance Regulation number 215 / PMK.03 / 2018 can be concluded that if the taxpayer choose to calculate the tax using Income Tax at the rate of Article 17 of the Income Tax Law, or has passed a certain gross circulation amount (Rp.4,800,000,000.00), or has passed a certain period of time required in Government Regulation number 23 of 2018, then The installment of Article 25 income tax in one tax year is NIL.